Structural transect through Ellesmere Island (Canadian Arctic): superimposed Palaeozoic Ellesmerian and Cenozoic Eurekan deformation - Karsten Piepjohn; Werner von Gosen (2017)
The complete transect (Segment 1 to 5) through Ellesmere Island between the Arctic Ocean in the NNW and Kane Basin in the SSE.